PENGARUH KUALITAS PELAYANAN DAN CULTURE (Budaya) MELALUI KEPUASAN NASABAH TERHADAP LOYALITAS PENGGUNA NASABAH BANK PAPUA CABANG DIY - Wonda, pendiron (JURNAL EKOBIS DEWANTARA, 2024)
In the banking sector, service quality, culture, and customer satisfaction are key factors in building customer loyalty. This study aims to analyze the influence of service quality and culture through customer satisfaction on customer loyalty at Bank Papua Branch DIY. A quantitative approach was used to collect data from the customers of Bank Papua Branch DIY. The results show that service quality and culture have a positive and significant impact on customer satisfaction. Additionally, customer satisfaction has a positive and significant impact on customer loyalty. Therefore, the bank is expected to continuously improve service quality and strengthen culture to enhance customer satisfaction and loyalty.